(3GdeUHGM GdefjQ aj ZQjH GdTQM GdcHjQs - (3CMeO Hf eMeO Gdajheis; (3YHO GdcQje Hf eMeO Hf YHO GdcQje, CHh GdbGSe GdQGaYj GdbRhjfj,J (B623 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejfhHYO aEfi cfJ LeYJ cJGHkG ai ZQjH TQM GdhLjR ddQGaYi s
(3BNQgG (B:s
(3djS GdaGVd ef dGjZdW Hd GdaGVd ef jYO ZdWg hfSCd Gddg MSf GdYGbHI s
(3GdfSNI HgG MhGTs
(3GdhLjR ddZRGdis
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B55 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B3s
Keywords: (3GddZIs